Slovácké divadlo II. - Lososová, Ivana (Vysoké učení technické v Brně. Fakulta architektury)
Diplomová práce se zabývá problematickou situací Slováckého divadla v Uherském Hradišti. Progresivní divadelní soubor dnes sídlí v budově bývalé sokolovny, která není schopná kapacitně ani technicky vyhovět nárokům komplikovaného divadelního provozu. Organismus divadelního souboru je také narušen odloučením studiové scény mimo hlavní areál divadla. Projekt zkoumá možnosti přesunu divadla do nové budovy, která je umístěna ve Smetanových sadech, v těsné blízkosti historického jádra Uherského Hradiště. Návrh budovy reaguje na prostředí regionálního města, potřeby konkrétního divadelního souboru a moderní divadelní postupy podložené analýzou české divadelní architektury.

The main topic of this diploma thesis is to solve problematic situation of the Slovac Theatre in Uherske Hradiste. Today, the progressive theater ensemble is housed in a former Sokol‘s building, which is not capable of fullfilling requirements of a complicated theatrical structure. The theater ensemble's organism is also disturbed by the separation of the studio scene outside the main theater area. The project explores the possibilities of moving the theater to a new building, which is located in Smetanovy sady, close to the historical centre of Uherske Hradiste. The design of the building responds to the environment of the regional city, the needs of a specific theater ensemble and modern theatrical procedures supported by the analysis of Czech theater architecture.
Theatre of Slovácko II
Keywords: divadlo; Slovácké divadlo; divadelní architektura; Uherské Hradiště; kultura; theatre; Slovacko theatre; theatre architecture; Uherske Hradiste; culture